Towards Sustainable Road Infrastructure Delivery in Nigeria - Oraegbune, O. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Due to current Federal Government infrastructure transformation policy agenda and economic development growth, there is a lot of pressure on Nigeria’s infrastructure, especially on roads. The construction of roads is capital intensive requiring long-term financial supports. The aim of this paper is to investigate the theory and practice that adopt sustainability concept at road and general infrastructure delivery in Nigeria. Multi-Criteria Decision Model or Method was used (Weighted Sum Model) for sustainability index. The mathematical model for computing the sustainability index in achieving the required result was formulated. Additionally, a cognitive/reasoning map system was used as decision aid. The result shows that sustainability criteria and indicators are chosen based on the project specific or regional priorities or needs. The study also showed that there is no systematic method of sustainability appraisal in Nigerian construction industry. It proposed both multi-criteria method of analysis and cognitive/reasoning map because of their mathematical foundation and practical applications, and recommends that sustainability drivers should be integrated with their different perceptions and priority needs. It also recommended the introduction of Sustainability Impact Assessment.